Prevalence of Treponemaspp. in endodontic retreatment-resistant periapical lesions - Tiago Pereira ROSA; Fernanda Graziela Corrêa SIGNORETTI; Francisco MONTAGNER; Brenda Paula Figueiredo de Almeida GOMES; Rogério Castilho JACINTO (Sociedade Brasileira de Pesquisa Odontológica, 2015)
This study investigated the presence of the Treponema species in longstanding endodontic retreatment-resistant lesions of teeth with apical periodontitis, the association of this species with clinical/radiographic features, and the association among the different target species. Microbial samples of apical lesions were collected from twenty-five adult patients referred to endodontic surgery after unsuccessful root canal retreatment. Nested-PCR and conventional PCR were used for Treponema detection. Twenty-three periradicular tissue samples showed detectable levels of bacterial DNA. Treponema species were detected in 28% (7/25) of the cases. The most frequently detected species were T. socranskii (6/25), followed by T. maltophilum (3/25), T. amylovorum (3/25), T. lecithinolyticum(3/25), T. denticola (3/25), T. pectinovorum (2/25) and T. medium(2/25). T. vicentii was not detected in any sample. Positive statistical association was found between T. socranskiiand T. denticola,and between T. maltophilumand T. lecithinolyticum. No association was detected between the presence of any target microorganism and the clinical or radiographic features. Treponemaspp.are present, in a low percentage, in longstanding apical lesions from teeth with endodontic retreatment failure.